The Analytical Theatre: New Art from Britain - Kalinovska, Milena; Newman, Michael (New York : Independent Curators Incorporated, 1987)
Allington, Edward ; Art & Language ; Chadwick, Helen ; Coleman, James ; Cragg, Tony ; Deacon, Richard ; Murphy, John ; Newman, Avis ; Richon, Olivier ; Wilkins, John
The Analytical Theatre: New Art from Britain, A traveling exhibition organized and circulated by Independent Curators Incorporated, New York. Akron Art Museum, Akron, Ohio, February 6 - March 29, 1987 ; Alberta College of Art Gallery, Calgary, Alberta, November 26 - December 19, 1987 ; University Art Museum, California State University, Long Beach, California, January 26 - March 6, 1988 ; Institute of Contemporary Art, University of Pennsylvania, Philadelphia, Pennsylvania, October 12 - November 27, 1988
boek
Keywords: Groot-Brittannië